Sistem Pendukung Keputusan Untuk Menentukan Eco Office Award Pada Dinas Lingkungan Hidup Kabupaten Asahan Dengan Metode MFEP - Ihsanul Fikri; Iqbal Kamil Siregar; Nurkarim Nehe (Forum Kerjasama Pendidikan Tinggi, 2022)
The Asahan Regency Environmental Service is the result of a government agency which is the implementing element of the Regional Government in the field of the Environment. As for determining the Eco Office Award at the Environmental Office of Asahan Regency, where the process of assessing the work environment of each office is carried out by providing a report that is assessed by the environmental team, where the assessment report determining the Eco Office Award is still carried out by file collection and archived so that there may be inaccuracies in determining the Eco Office Awards are very high. In this study, the MFEP method was chosen to determine the decision assessment to determine the Eco Office Award. This method is more efficient than other methods included in the completion of Multi Attribute Decision Making (MADM). The reason is because the time required for the calculation is shorter. As can be obtained from the calculation of the alternative evaluation of Determining the Eco Office Award above, the decision to choose from the alternative is chosen from the highest value, then PT. Pos Indonesia Range